WHO BENEFITS MORE FROM DIRECT MARKETING SCHEMES? THE CASE OF ARABICA COFFEE COOPERATIVE AND ITS FARMERS MEMBER IN RURAL INDONESIA - Boris KAIDO; Katsuhito FUYUKI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Cooperatives play a prominent role in the agricultural sector, both in developed and developing countries. This study aimed to examine the cost and profitability of direct marketing between a cooperative and its farmers member. Data were collected based on a direct face-to-face economic survey using the purposive sampling method for a case study of Alam Kerinci cooperative, the biggest arabica coffee cooperative in Kerinci Regency, Indonesia, and its farmers. Cost-profitability calculation analysis was conducted, and the non-parametric Mann-Whitney test was used to examine the differences between the inputs, variables, cost, and profitability. The results highlighted that the cooperative’s variable cost was enormous, reaching 98.15% of its total costs, and its major component was purchasing red cherry beans, with a value of 57.80%. For farmers, the largest cost was variable cost (79.51%), with hired labor as the major component, reaching 31.47%. The profitability for the cooperative and its farmers can be demonstrated by the monthly net profit, which was IDR 96,787,500 and IDR 1,714,108, respectively. This confirmed that the cooperative’s profit was larger than that of farmers. However, the farmers’ cost-benefit ratio was higher than the cooperative’s, at 0.87. The implication of this study is that farmers benefitted economically from this scheme. The study makes a novel contribution as it shows that a direct marketing scheme with the cooperative is beneficial to farmers.